Límites del marco lógico y deficiencias de la evaluación tradicional de la cooperación al desarrollo para medir impacto - Vázquez-De Francisco, María José; Torres-Jiménez, Mercedes; Caldentey-Del Pozo, Pedro (Revista Iberoamericana de Estudios de Desarrollo, 2015)
Measuring impact has traditionally been the weakest step in the traditional evaluation of aid, because of its costs, methodologies, time and difficulties in attributing effects. But this exercise is necessary both in technical and moral terms, especially for those benefitting from the aid. The use of a logical framework as the most accepted tool for aid management has not helped in impact measuring, which is a revealing reflection of aid effectiveness. It is precisely those international commitments for aid effectiveness that highlight the limitations of traditional evaluation practices. This paper intends to reflect upon those limits through a systematic academic review, and will propose a conceptual revision of impact evaluation indicators.